Circular ZDHHC11 supports Burkitt lymphoma growth independent of its miR-150 binding capacity - Yichen Liu; Xing Zhao; Annika Seitz; Annie A. Hooijsma; Reyhaneh Ravanbakhsh; Sofia Sheveleva; Debora de Jong; Jasper Koerts; Agnieszka Dzikiewicz-Krawczyk; Anke van den Berg; Lotteke J. Y. M. Ziel-Swier; Joost Kluiver (Scientific Reports, 2024)
Abstract We previously showed that MYC promoted Burkitt lymphoma (BL) growth by inhibiting the tumor suppressor miR-150, resulting in release of miR-150 targets MYB and ZDHHC11. The ZDHHC11 gene encodes three different transcripts including a mRNA (pcZDHHC11), a linear long non-coding RNA (lncZDHHC11) and a circular RNA (circZDHHC11). All transcripts contain the same region with 18 miR-150 binding sites. Here we studied the relevance of circZDHHC11, including this miR-150 binding site region, for growth of BL cells. CircZDHHC11 was mainly present in the cytoplasmic fraction in BL cells and its localization was not altered upon miR-150 overexpression. Knockdown of circZDHHC11 caused a strong inhibition of BL growth without affecting the expression levels of MYC, MYB, miR-150 and other genes. Overexpression of circZDHHC11 neither affected cell growth, nor rescued the phenotype induced by miR-150 overexpression. Genomic deletion of the miR-150 binding site region did not affect growth, nor did it change the effect of circZDHHC11 knockdown. This indicated that the miR-150 binding site region is dispensable for the growth promoting role of circZDHHC11. To conclude, our results show that circZDHHC11 is a crucial factor supporting BL cell growth independent of its ability to sponge miR-150.